Team handball goalkeeper and perceptual skills: kid's training proposal - Ignacio Romero Novoa (Federación Extremeña de Balonmano; University of Extremadura, 2012)
Goalkeepers are crucial in team handball with a great relevance on results, but goalkeeper's training has been traditionally based on experience and intuition. It's particular actions needs specially perceptual skills, so this study makes a review of those abilities and their applied studies for making a proposal in perceptual skills training. Key words: Perception, team handball, goalkeeper, perceptual training